2020
DOI: 10.1097/pcc.0000000000002306
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Utilization and Complications in the Pediatric Cardiac ICU: A Report From the Pediatric Cardiac Critical Care Consortium (PC4)*

Abstract: Objectives: Current central venous catheter utilization in patients within pediatric cardiac ICUs is not well elucidated. We aim to describe current use of central venous catheters in a multi-institutional cohort and to explore the prevalence and risk factors for central line–associated thrombosis and central line–associated bloodstream infections. Design: Observational analysis. Setting: Pediatric Cardiac C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…While in one study 7% of adolescents with MIS‐C were reported to have developed deep venous thrombosis or pulmonary embolism, other large cohorts have demonstrated rates closer to 0–2% (5–7). This rate of thrombotic events is similar to that observed in children without MIS‐C who have central venous lines, and many children with MIS‐C require intensive care measures and central venous access (8). d ‐dimer levels are frequently elevated in MIS‐C patients, but it is unclear if this laboratory parameter is directly reflective of hypercoagulability risk.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…While in one study 7% of adolescents with MIS‐C were reported to have developed deep venous thrombosis or pulmonary embolism, other large cohorts have demonstrated rates closer to 0–2% (5–7). This rate of thrombotic events is similar to that observed in children without MIS‐C who have central venous lines, and many children with MIS‐C require intensive care measures and central venous access (8). d ‐dimer levels are frequently elevated in MIS‐C patients, but it is unclear if this laboratory parameter is directly reflective of hypercoagulability risk.…”
supporting
confidence: 66%
“…We read with great interest the article by Dong et al on the role of STAT4 activation in Tfh cell production of IL-21 and IFNγ in lupus (8). The authors present exhaustive data demonstrating that type I IFN can maintain STAT4 activation in Tfh cells and Tfh cell production of IL-21 and IFNγ as the disease in lupus-prone mice progresses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Central access via upper-extremity peripherally inserted central catheter or internal jugular vein was preferred based on consensus in order to preserve femoral vein access. This preference was secondary to concern for thrombosis inherent to femoral vascular access devices and the potential need for future femoral venous access for cardiac catheterization procedures [1,3,4]. Subclavian venous access was rated uncertain by the panel, due to the limitations of ultrasound use with this placement technique and the variable experience of operators.…”
Section: Resultsmentioning
confidence: 99%
“…DiPietro and colleagues previously evaluated multi-institutional central venous access device use in patients in North American paediatric cardiac intensive care units [4]. Within the cohort, central venous access device location varied extensively based on physiology and need for cardiac procedure.…”
Section: Introductionmentioning
confidence: 99%